Capital Inflows to Latin America : The 1970's and the 1990's - Reinhart, Carmen (IMF Working Papers; Working Paper ;, 1992)
During the past two years Latin America has received sizable international capital inflows. This paper compares the recent experience with that of the late 1970s. The analysis examines differences and similarities between the two episodes in three broad areas: domestic macroeconomic conditions in the recipient countries at the outset of both episodes, the behavior of the external factors that influence the international allocation of capital, and the response of key macroeconomic variables, such as the real exchange rate, reserves, and stock prices. The paper aims at assessing how vulnerable these economies are to an unexpected and swift reversal in capital inflows, and whether there are signs that the vulnerability has changed appreciably over time.